Three‐state time‐modulated array‐enabled directional modulation for secure orthogonal frequency‐division multiplexing wireless transmission - Gaojian Huang; Yuan Ding; Shan Ouyang; Vincent Fusco (IET Communications, 2022)
Abstract Recent works have shown that by using time‐modulated arrays (TMAs), directional modulation (DM) physical‐layer secured transmitters for orthogonal frequency‐division multiplexing (OFDM) wireless data transfer can be constructed. In this paper, three‐state TMAs are introduced for OFDM DM systems which allow more flexible manipulation of the injected orthogonal artificial noise and hence improve security. In particular, this paper presents for the first time both static and dynamic three‐state time‐modulated OFDM DM systems. Simulated bit error rate (BER) spatial distributions are shown for various system configurations in order to illustrate representative examples of secrecy performance enhancement that can be achieved by the proposed transmitter arrangement.